Water column raw data (Kongsberg EM122 entire dataset) of RV MARIA S. MERIAN during cruise MSM111 - Boris Dorschel; Katharina Teresa Streuff; Gavin D extquotesingleMello; Simon Dreutter; Michal Kucera (PANGAEA, 2023)
Water column data were collected with RV Maria S. Merian along parts of the route of cruise MSM111 and data acquisition was continuously monitored during the survey. Multibeam sonar system was Kongsberg EM122. The raw multibeam sonar data in Kongsberg multibeam processing format (.all) and water column data (.wcd) were recorded with Kongsberg SIS. Water column data needs to be processed in combination with the corresponding bathymetry files. Raw data files can be processed using software packages like CARIS HIPS/SIPS.